Management of viral and leaf spot disease complexes in organic farming of blackgram - and SANDEEP KUMAR SHARMA, AMIT TRIVEDI*, S.K. SHARMA, O.P. AMETA (Indian Phytopathology, 2014)
Organic farming is gaining global importance with increasing awareness of the consumers towards quality products free from chemical residues, pesticide and the environmental protection. Black gram (Vigna mungo L.) is one of the important pulse crops grown throughout the country. Sustainable black gram production is continuously challenged from several diseases of which viral and leaf spot disease complexes are of economic importance. Field experiments were conducted during kharif 2010, 2011 and 2012 to develop a suitable organic module to manage these diseases and improve productivity of blackgram. The module consisting of soil application of neem cake @ 2 q ha-1 + one foliar spray of BD-501 (1g/13 L) at 20 DAS + one foliar spray of neem oil @ 2% at 25 days + two sprays of BD 501 or neem oil significantly reduced the incidence of viral and leaf spot disease complexes and increased the yield attributes and yield of blackgram. Viral incidence in various treatments ranged between 3.12 and 3.32% compared to 6.12% in untreated control. Two sprays of BD-501 (1g 13L-1) proved highly effective for the management of leaf spot complex. The lowest leaf spots (PDI 28.25) and maximum seed yield (9.26 q ha-1) was recorded with the application BD-501 followed by Neem oil (PDI 29.58 and seed yield 8.39 q ha-1) as compared to control (PDI 63.42 and seed yield 7.24 qha-1). The IDM module resulted in 1.5 times higher B: C ratio over the untreated control.